Mentors Supporting Nurses Transitioning to Primary Healthcare Roles: A Practice Improvement Initiative - Rachel Rossiter HScD, RN; Tracy Robinson PHD, BA Hons, RN; Rebekah Cox RN; Lisa Collison RN; Danny Hills PhD, RN (SAGE Publishing, 2024)
Introduction Effective primary healthcare services have been identified by the World Health Organization as the most equitable approach to enhancing universal healthcare. Robust models of mentoring for registered nurses (RNs) transitioning to primary healthcare roles have yet to be described in the Australian context. A robust mentoring model can support RNs to fulfill their potential, bridging the gap between theory and practice. In 2015, the peak body for nurses in primary health care (PHC) began developing a transition to practice program, including embedded mentoring to support newly graduated and more experienced registered and enrolled nurses. This quality improvement study reports the experiences and perspectives of nurses participating as mentors in two separate offerings of the program delivered between 2019 and 2021. Method A two-phase concurrent mixed methods evaluation utilized data from pre- and post online surveys and post program meetings. Quantitative items underwent descriptive analyses. Thematic analysis of free-text responses and comments was conducted independently by two researchers. Mentors voluntarily provided self-report data and were informed that data is routinely collected to support continuous quality improvement processes for all programs. An Information Sheet informed mentors of data usage, confidentiality, and options to withdraw without penalty from the program at any time. Results Seventy-nine mentors were recruited to support two groups of nurses ( N  = 111). Mentor self-rated overall satisfaction with program participation was 86.67% (very or extremely satisfied). Mentors described being "witness to mentee growth," "having facilitated access to learning" and receiving "unexpected benefits" including personal and professional growth and enhanced enthusiasm for their role in PHC. Conclusion The embedded mentoring reported in this article combined a focus on skills acquisition and professional identity with the provision of a range of resources and support activities. Sustainable mentoring programs will be an important mechanism for supporting the expanding roles required of nurses working in primary health.